Using different Pitman-closeness techniques for the linear combination of multivariate forecasts - Thomas Wenzel (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
We specify the Pitman-closeness criterion for the evaluation of multivariate forecasts in three categories. This is done closely to the definition of covariance adjustment techniques analysed in other articles. We also apply the Pitman-closeness techniques to an example dealing with German economic data.
Keywords: 519; Pitman-closeness; multivariate forecasting methods; covariance adjustment